2013
DOI: 10.22146/ijc.21331
|View full text |Cite
|
Sign up to set email alerts
|

Design of New Potent Insecticides of Organophosphate Derivatives Based on QSAR Analysis

Abstract: Design of new potent insecticide compounds of organophosphate derivatives based on QSAR (Quantitative Structure-Activity Relationship) analytical model has been conducted. Organophosphate derivative compounds and their activities were obtained from the literature. Computational modeling of the structure of organophosphate derivative compounds and calculation of their QSAR descriptors have been done by AM1 (Austin Model 1) method. The best QSAR model was selected from the QSAR models that used only electronic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Compositions by this model was designed and tested in silicon. The results revealed that the insecticidal activity of newly synthesized compounds is greater than the existing insecticides [41]. Insecticidal effect of another class of derivatives was investigated on the AChE of housefly.…”
Section: Comparison Of Qsar Model Of Human With Qsar Model Of X Lutementioning
confidence: 99%
“…Compositions by this model was designed and tested in silicon. The results revealed that the insecticidal activity of newly synthesized compounds is greater than the existing insecticides [41]. Insecticidal effect of another class of derivatives was investigated on the AChE of housefly.…”
Section: Comparison Of Qsar Model Of Human With Qsar Model Of X Lutementioning
confidence: 99%
“…They may have adverse impacts on various groups of soil microbes, wild animals, and also humans, through environmental contamination, or residues in food and feedstuff (Torres-Palma and Serna-Galvis 2018; Bora et al 2020;Toropov et al 2017Toropov et al , 2018. Experimental data on these chemicals can be used to improve the design of new pesticides, moving towards safer, greener substances, considering their adverse effects on humans and ecosystems (Mudasir et al 2013;Wibowo et al 2017). Furthermore, organophosphates are chemical warfare tools (Mendonca et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The best QSAR model showed that 74.1% of validation set was correctly predicted. [22] In a research, Hamadache and colleagues developed a validated QSAR model to predict acute oral toxicity of some pesticides to rats. [23] They found that the best results were obtained with the Quasi Newton back propagation (BFGS) algorithm Artificial Neural Network (ANN) model.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation models between descriptors and insecticide activity were evaluated by multiple linear regression (MLR) analysis using software SPSS 13 on the Backward method. The best QSAR model showed that 74.1% of validation set was correctly predicted . In a research, Hamadache and colleagues developed a validated QSAR model to predict acute oral toxicity of some pesticides to rats .…”
Section: Introductionmentioning
confidence: 99%